Countermeasure strategies for law enforcement of illegal online toto gambling: Study at Central Maluku Police - Adam, Sherly; Salmon, Harly Clifford Jonas; Makaruku, Steven (Gema Wiralodra, 2023)
Online lottery is one of the crimes we usually call cyber crime, so apart from being charged under the Criminal Code, online lottery gambling games can also be set under Article 27 paragraph (2) in conjunction with Article 45 of Law Number 11 of 2008 concerning Information and Transactions. Electronic. The duties, functions, and responsibilities of the National Police, one of which is enforcing the law, where the National Police, especially the Central Maluku Police, plays a role in tackling crime, one of which is online lottery gambling. The aim of this research is to reveal a countermeasure strategy for enforcing online lottery gambling laws carried out by the Central Maluku Police. The type of research used is empirical legal research. Central Maluku Police research location. The sample, respondents, and population are the head and members of the General Crimes Unit of the Central Maluku Police. Data sources are primary data and secondary data. Data collection techniques through interviews and observation. Qualitative data processing and analysis techniques. The results of the research show that the strategy for dealing with online lottery gambling law enforcement carried out by the Maluku Police is to increase human resource skills, increase facilities, or increase public legal awareness and maximize the role of the community. For this reason, it is hoped that the strategy to overcome online lottery gambling law enforcement carried out by the Central Maluku Police can tackle online lottery gambling so that the role and support of the government, law enforcement officials, and the community are also needed to realize the ideal and aspired online lottery gambling law enforcement.